2006
DOI: 10.1542/peds.2005-3109
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Sunburns, Sun Protection Practices, and Attitudes Toward Sun Exposure Protection and Tanning Among US Adolescents, 1998–2004

Abstract: A small reduction in sunburn frequency and modest increases in sun protection practices were observed among youth between 1998 and 2004, despite widespread sun protection campaigns. Nevertheless, the decrease in sunburns among younger teens may be cause for optimism regarding future trends. Overall, there was rather limited progress in improving sun protection practices and reducing sunburns among US youth between 1998 and 2004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
132
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(140 citation statements)
references
References 49 publications
6
132
1
1
Order By: Relevance
“…Survival from late stage disease remains poor despite significant research efforts on a variety of treatment options 3 . Primary prevention strategies, focusing on reducing unnecessary ultraviolet (UV) exposure and other UV protection behaviors, can be difficult to implement [4][5][6][7] . Early detection, when melanoma is thin and confined to the skin, may be the best chance to positively impact melanoma mortality and is feasible through simple visual inspection, which is paramount to effective secondary prevention strategies 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Survival from late stage disease remains poor despite significant research efforts on a variety of treatment options 3 . Primary prevention strategies, focusing on reducing unnecessary ultraviolet (UV) exposure and other UV protection behaviors, can be difficult to implement [4][5][6][7] . Early detection, when melanoma is thin and confined to the skin, may be the best chance to positively impact melanoma mortality and is feasible through simple visual inspection, which is paramount to effective secondary prevention strategies 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies have also concluded that females have pore positive attitudes against sun protection measures that may result from cultural reasons, since females are urged to look after their appearance much more compared to males (Lowe et al, 2000;Geller et al, 2005;Cokkinides et al, 2006;Livingston et al, 2007).…”
Section: Assessment Of Knowledge and Attitudes Before And After The Imentioning
confidence: 71%
“…Also after the program, many more students knew what the correct SPF for them was (56.6% vs 27.1%). Several international studies have also confirmed that knowledge about the correct sunscreen increases greatly especially in combination with an education program (Geller et al, 2005;Buller et al, 2006;Cokkinides et al, 2006;Livingston et al, 2007;Murray, 2013).…”
Section: Assessment Of Knowledge and Attitudes Before And After The Imentioning
confidence: 92%
See 1 more Smart Citation
“…Evidence suggests adolescents have low levels of sun protection behaviours and high levels of sun exposure and sunburns (e.g., Cokkinides et al, 2006;Stanton et al, 2004). During adolescence sun exposure and sun protection knowledge increase with age, yet there is a decrease in sun protection behaviours (Broadstock et.…”
mentioning
confidence: 99%